Terpenoids with potent antimycobacterial activity against Mycobacterium tuberculosis from Trigonostemon reidioides roots - Kaemchantuek, Praphakorn; Chamulitrat, Walee (Tetrahedron, 2017)
Phytochemical investigation of Trigonostemon reidioides roots led to the isolation of fourteen compounds. These included six new diterpenoids, trigonoreidons A−F (1−6), together with eight known diterpenoids 7−14. The structures of the new compounds were elucidated by spectroscopic techniques and the absolute configuration at the asymmetric carbon was determined by the modified Mosher's method. The structure of trigonoreidon B (2) was confirmed by X-ray crystallographic analysis. The known compounds were identified by comparison of the spectroscopic and physical data with those of reported values. The isolated compounds were evaluated for antimycobacterial activity against Mycobacterium tuberculosis. Among the compounds that exhibited antimycobacterial activity, the diterpenoids rediocide C (12) and rediocide G (14) were the most active compounds, with the MIC value of 3.84 μM.